Association of MBL2 gene exon 1 variants with autoimmune thyroid disease in Brazilian patients. - Filho, C B; Rodrigues, F F; Segat, L; Fonseca, A M; Araujo, J; Arahata, C; Pontes, L; Vilar, L; de Lima Filho, J L; Crovella, S (Int J Immunogenet, 2012)
We investigated the association between MBL2 gene exon 1 functional polymorphisms and autoimmune thyroid disease (AITD) in 163 Brazilian patients (87 with Hashimoto thyroiditis, HT; 76 with Graves' disease) and 214 healthy controls. Individuals carrying MBL2 O allele are at higher risk of developing AITD (OR = 1.58, 95% CI: 1.11-2.26; P-value = 0.009) and HT (OR = 1.67, 95% CI: 1.09-2.55; P-value = 0.013) as suggesting a possible role for mannose-binding lectin in influencing disease susceptibility.
Keywords: Adolescent; Adult; Brazil; Case-Control Studies; Child; Child, Preschool; Exons; Female; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Testing; Graves Disease; Hashimoto Disease; Humans; Infant; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Single Nucleotide; Young Adult